Macphail (1987) Revisited: Pigeons Have Much Cognitive Behavior in Common With Humans - Zentall, Thomas R. (Frontiers in Psychology, 2021)
The hypothesis proposed by Macphail (1987) is that differences in intelligent behavior thought to distinguish different species were likely attributed to differences in the context of the tasks being used. Once one corrects for differences in sensory input, motor output, and incentive, it is likely that all vertebrate animals have comparable intellectual abilities. In the present article a number of tests of this hypothesis are provided with pigeons. In each case, either there is evidence for the cognitive behavior, or the pigeons suffer from biases similar to those of humans. Thus, Macphail’s hypothesis offers a challenge to researchers to find the appropriate conditions to bring out in the animal the cognitive ability being tested.